Analysis of the Relationship Between Technopreneurship Learning and Technopreneurship Intention through Entrepreneurship Self-Confidence - Choirunnisa, Salsabila Safitri; Murwani, F. Danardana; Wardana, Ludi Wishnu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the relationship between technopreneurship learning and technopreneurship intention by encouraging entrepreneurial self-confidence in vocational high school students in the Pujon District. The method used is quantitative research with descriptive and explanatory design. The data collection technique was purposive sampling, with 190 active students registered in three vocational high schools. Data were collected using questionnaires distributed online. The data analysis technique used Smart PLS, which includes outer model testing, inner model testing, and hypothesis testing. The study results indicate that hypotheses 2 to 4 are accepted, which means a significant positive effect exists between technopreneurship learning and entrepreneurial self-confidence and technopreneurship intention. However, the first hypothesis needs to be accepted, indicating that technopreneurship learning does not significantly affect technopreneurship intention.